RNA polymerase III autoantibodies may indicate renal and more severe skin involvement in systemic sclerosis. (24th October 2015) - Terras, Sarah; Hartenstein, Hans; Höxtermann, Stefan; Gambichler, Thilo; Kreuter, Alexander
Abstract: Background: Systemic sclerosis (SSc) is a multiorgan autoimmune disorder characterized by sclerosis of the skin and organs as well as the presence of antinuclear autoantibodies. Several types of antinuclear autoantibodies have been described in SSc, associated with distinct disease entities and differences in prognosis. Methods: The aim of this study was to screen for the presence of antibodies reacting with RNA polymerase III (anti‐RNAP3) in a large cohort of patients with SSc treated at a tertiary referral center and to evaluate correlations with disease severity. Results: Anti‐RNAP3 antibodies were detected in 11 of 158 patients (7.0%). Eight of the 11 (72.7%) anti‐RNAP3‐positive patients had diffuse cutaneous SSc ( P < 0.01). A higher modified Rodnan skin score, associated with diffuse SSc, correlated with the presence of anti‐RNAP3 ( P < 0.0001). The detection of anti‐RNAP3 antibodies strongly correlated with the presence of renal involvement ( P < 0.0001). The odds ratio of RNAP3‐positive patients to develop renal involvement was 80.1 (95% CI 9.3–690.1). Conclusions: This study demonstrates that the detection of anti‐RNAP3 antibodies in patients with SSc correlates with renal crisis and severe cutaneous involvement. The possibility to detect specific antibodies with a prognostic value can lead to a better risk management of patients with SSc.